EVALUATION OF PATIENT HANDLING’S WORK POSTURE AND MUSCULOSKELETAL DISORDERS OF NURSES IN ABC HOSPITAL - Silvi Rushanti Widodo; Sri Rahayuningsih (Center for Study and Journal Management FTI UMI, 2023)
The main problem for nurses that often causes complaints of musculoskeletal disorders is when carrying out patient appointments or patient handling. This is because the work performed varies depending on the needs of the patient. The purpose of this study is to determine the prevalence of symptoms of musculoskeletal disorders in nurses when removing patients from Hospital A. This study uses a cross sectional approach which is observational descriptive. The population of this study were all nurses at Hospital A. The sample taken was purposive sampling. The variables to be studied are the work posture of nurses when carrying out patient handling and complaints of musculoskeletal disorders. By measuring work posture using the RULA (Rapid Upper Limb Assessment) and REBA (Rapid Entire Body Assessment) methods. And complaints of musculoskeletal disorders are measured using the Nordic Body Map. The greatest percentage of body part complaints that nurses feel when lifting patients is in the lower back, which is 64%. The results of observations of work posture on average needed immediate improvement, but the most immediate changes to be made were in the patient placement section.